Imanuel e espírito de Iahweh: leitura e releitura do messianismo em Isaías (7,10-17; 8,23-9,6; 11,1-9) - SANTOS, Suely Xavier dos (2011)
The object of research of this dissertation are perícopes of Isaiah 7,10-17; 8,23- 9,6 and 11,1-9. In this we meet the principal point of the messianic thought of Isaiah. It is important to observe that the isaian messianism comes from the conception of messiah that comes to govern from the right and justice, and, thus, to establish the peace. The messianism presented for this prophet don’t part of the spheres of the kingdom power, but of the small and fragile persons of the society, endowed with the spirit of Yahweh. It has to be distinguished that the prophecy of Isaiah is a watershed with respect to the messianic theology in the Kingdom of the South, especially the prophets after him. In Isaiah, we meet the rupture with the ruling classes and a warlike messianism. The proposal of this prophet points to a fragile messiah, but that is moved by the blow, by the movement of Yahweh and his action. And thus, Isaiah opens the doors for understanding a poor messiah, as Zechariah recognize, a messiah in service, presented for the Second-Isaiah, or who knows a shepherd messiah, as as considered by Micah and Ezekiel and received well for the traditions of the first century (Jo 10,10). The messiah in Isaiah have “names and adjectives”: Imanuel, child, root of Jessé, but do not have face, do not have geographic localization, is not fit in the messianic type since the davidic of Jerusalem. These messiah can be found at any time with any face, by that is important a new reading messianic presented in texts of the current Christianity. Many of inspired them in the isaian prophecy of 8º. century B.C.(AU)